Transition readiness in adolescents and young adults with chronic rheumatic disease in Oman: today's needs and future challenges - Reem Abdwani; Rumaitha Al Sabri; Zawan Al Hasni; Seyad Rizvi; Humaid Al Wahshi; Batool Al Lawati; Safiya Al Abrawi; Yassir Wali; Mona Al Sadoon (BMC, 2022)
Abstract Introduction In Oman, the ""transition" of health care of adolescents to adult care occurs at a young age, like many other GCC countries for cultural reasons. In order to address this concern, this study was conducted to determine the transition readiness skills of adolescents and young adults with childhood onset rheumatic diseases using a cross-cultural adaptation of the UNC TRxANSITION scale. Methods We used a professionally translated/back translated, provider-administered UNC TRxANSITION Scale. This 32-question scale measures HCT in 10 domains including knowledge about diagnosis or treatment, diet, reproductive health, school/work, insurance, ability to self-manage and identification of new health providers. The maximum transitional score of 10, was categorized as low (1-4), moderate (4 - 7) and high (7 -10) transitional readiness scores. Results We enrolled 81 Omani adolescents and young adults (AYA) with chronic childhood onset rheumatic diseases. The cohort consisted of 79% females, with mean age of 15.8 years (± 3.53) and mean disease duration of 6.95 years (± 4.83). Our cohort's overall mean score is low 5.22 (±1.68). Only 14.8% of the cohort achieved a high transition score (≥7). Significant direct relationship was observed between age and the mean transition readiness score (r = .533, P < .001). The mean transition readiness score in the younger age group (10-13 years) was 4.07 (±1.29), the middle age group (14-18 years) was 5.43 (±1.27), while the older age group (19-21 year), was 6.12 (±1.81). Mean transition score of youngest age group was found to be significantly lower than the other two age groups (p = .003). Conclusion Overall, the transition readiness of AYA in Oman is low compared to other western countries indicating the need to initiate a health care transition preparation program for patients with chronic diseases across the country. In addition, we need to establish regional guidelines to address the transfer and transition policies to be in line to international recommendations. As transition continues after transfer, and is preferably guided by adolescent developmental status rather than chronological age, it would be preferable to refer to the transition and transfer policies 9rather than transitional age policy) to be in line to international recommendations.